A pathogenic mechanism leading to partial lipodistrophy and prospects for pharmacological treatment of insulin resistance syndrome - Maraldi, Nadir M.; Capanni, Cristina; Mattioli, Elisabetta; Columbaro, Marta; Squarzoni, Stefano; Parnaik, Weena K.; Wehnert, Manfred; Lattanzi, Giovanna (Acta Biomedica Atenei Parmensis, 2007)
The understanding of a common complex phenotype such as insulin resistance can be favoured by evaluation of monogenic syndromes. Clinical definition, pathogenesis, and therapeutical strategies for the insulin resistance syndrome can thus be improved by the characterization at the molecular genetic level of monogenic forms of lipodystrophies. Here we report experimental evidence on the pathogenic mechanism underlying insulin resistance in a rare form of laminopathy, due to mutation of the LMNA gene coding for lamin A/C, the Dunning-type familial partial lipodystrophy (FPLD). The defect, consisting in the intranuclear accumulation of mutant unprocessed precursors of lamin A, reduces the amount of the DNA-bound adipocyte transcription factor sterol regulatory element binding protein 1 (SREBP1) and lowers the peroxisome proliferator-activated receptor (PPARg) expression, causing the impairment of pre-adipocyte differentiation. The treatment with the PPARg ligand troglitazone (TDZ) is able to rescue the adipogenic program. Since FPLD recapitulates the essential metabolic abnormalities of the common insulin resistance syndrome, the beneficial effects of TDZ on monogenic lipodystrophies might provide a clue as to the future treatment strategies also for the common syndrome of insulin resistance.